2022
DOI: 10.1021/acsestwater.2c00216
|View full text |Cite
|
Sign up to set email alerts
|

Advancement and Challenges in Municipal Landfill Leachate Treatment–The Path Forward!

Abstract: Although landfill leachate is a small volumetric fraction compared to municipal wastewater, its complexity raises concerns for researchers and practitioners. Emerging and novel treatment technologies are being investigated to address landfill leachate treatment challenges. In the past decade, leachate research shifted from the removal of contaminants to the simultaneous recovery of resources and removal of contaminants. While resource recovery is appealing, it is also questionable due to the economic feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…In general, leachate consists of dissolved organic matter, xenobiotic organic compounds, heavy metals, and different anions and cations. The chemical characteristics of leachate in Bangladesh are comparable to those in other parts of the world (Figure ). The median concentrations of Fe (17.20 mg L –1 ), Cu (0.93 mg L –1 ), TSS (1395.50 mg L –1 ), BOD (216 mg L –1 ), COD (1571 mg L –1 ), and TDS (6970 mg L –1 ) in leachate are greater than the Bangladesh inland water discharge limits (Figure and Tables S3 and S4). The highest concentrations of these parameters are significantly higher than the median values and the discharge limits.…”
Section: Industrial Wastewater Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…In general, leachate consists of dissolved organic matter, xenobiotic organic compounds, heavy metals, and different anions and cations. The chemical characteristics of leachate in Bangladesh are comparable to those in other parts of the world (Figure ). The median concentrations of Fe (17.20 mg L –1 ), Cu (0.93 mg L –1 ), TSS (1395.50 mg L –1 ), BOD (216 mg L –1 ), COD (1571 mg L –1 ), and TDS (6970 mg L –1 ) in leachate are greater than the Bangladesh inland water discharge limits (Figure and Tables S3 and S4). The highest concentrations of these parameters are significantly higher than the median values and the discharge limits.…”
Section: Industrial Wastewater Characteristicsmentioning
confidence: 96%
“…from landfill leachate using advanced technologies. 43 Therefore, Bangladesh should consider the shortcomings of the conventional wastewater treatment plants in treating leachate 41 and address such shortcomings to improve the existing treatments. At the same time, the Bangladesh DOE should extend the list of leachate contaminants to include the emerging contaminants and start implementing regulatory discharge limits for such contaminants.…”
Section: Ongoing Research and Research Needs For Industrial Wastewate...mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of energy consumption, the chlorine-reuse process coupled with UV dechlorination consumed half the energy required to operate a conventional UV/EO process at 27.3 kWh•m −3 (7.5 and 19.8 kWh•m −3 for R 1 and R 2 , respectively) or 5.1 USD•m −3 . Although studies have suggested that Fenton's oxidation is cost-effective at 0.59−2.70 USD•m −3 in hybrid treatment lines, 4 such processes rely on coagulants, which return to the landfill, and introduce contaminants like iron and sulfate into the treated effluent. 50 Thus, the chlorinereuse process offers better prospects for cost reductions and scalability.…”
Section: Structural Comparisons Between Conventional Andmentioning
confidence: 99%
“…Plants that prefer on-site methods often implement membrane-based processes such as reverse osmosis (RO). 4 However, these methods are often cost-prohibitive, with operational costs between 6 and 7 USD•m −3 , which dissuade their implementation in many regions. 5 In addition, the RO modules generate brine that can be up to 20 times more concentrated than the original leachate feed, requiring costly treatment that can increase aquatic ecotoxicity according to life cycle assessments.…”
Section: ■ Introductionmentioning
confidence: 99%